Electronic Crime in the Sultanate of Oman: Challenges and legal solutions - Al Shibli, Abdullah bin Ali bin Salem (Journal of Economic, Administrative and Legal Sciences, 2019)
The purpose of the research was to identify the concept of cybercrime and its Characteristics, the role of the Omani Legislator to find the appropriate solutions towards this problem. The researcher used the descriptive approach to achieve the research objectives. The research results showed that the Omani Legislator was able to deal with new civilization development and challenges by updating Laws and Rules that combat all criminal types and especially the electronic and informational crimes. The cybercrimes punishments are ranging from financial fines to freedom- related penalties. The research has reached a number of recommendations, including: The importance of conducting studies based on the surveys field that deal with the types of electronic crimes committed such as: the number of perpetrators, their criminal motives, their nationalities and age groups in order to develop the laws currently in force in the Sultanate of Oman to cope with modern international laws at the same criteria. It’s very important to raise the awareness of society about the seriousness of electronic crimes, methods of committing them, its moral effectiveness and methods of prevention.